REORIENTASI ARAH KEBIJAKAN PENDIDIKAN TINGGI HUKUM DALAM UPAYA MEMBENTUK PENEGAK HUKUM PROFESIONAL - Syaifuddin Syaifuddin; Ade Kosasih (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2018)
Abstract: The phenomenon of caught red-handed operations against law enforcement is a manifestation of failure of legal higher education in producing professional law enforcements. The orientation of higher education law is only on both theoretical and practical competencies, while character education is improved. Therefore the policy of implementing legal higher education needs to be directed at character education through efforts in order to internalize idealism values such as justice, truth, honesty, kindness, responsibility, etc. into prospective graduates/students who will become law Enforcement Scholars. In addition, learning methods that tend to be conventional and monologue need to be replaced with methods that can stimulate students to be more critical, analytical, innovative and progressive. Keywords: Reorientation, School of Law, Professionalism